Miłość Boga w ujęciu J. Razingera/Benedykta XVI - Barth, Grzegorz (Verbum Vitae, 2013)
The article presents the subject of God’s love in J. Ratzinger/Benedict XVI’s interpretation. The theme of God’s love, according to Ratzinger, is not to be reduced to one of the many theological issues to be discussed. Pope puts the love of God at the center of the Christian life as a principle and interpretative key. It is no coincidence that the first encyclical Deus caritas est, inaugurating his pontificate, begins with the words which are the profession of faith in the name of God who is Love. This agapetological feature of the Papal reflection sets the frame of his theology and points at the sphere where it reaches its essence and consummation. The subject of God’s love is discussed in two parts of the article: the first one consists of the analysis of the three terms: eros, agape and caritas, which are the three aspects of love. The philosophical and biblical analysis of these expressions made by Benedict XVI allows him to extract the essence of divine love. In the second part of the present article, the three moments reflecting the whole dynamics of love in the teaching of the Pope will be discussed: the source of love in the Triune God (1), the concretization and the fullest revelation of love in the person and work of Jesus Christ (2), and the relationship between the love of God and the love of man (3). The latter ultimately becomes a human response based on the primacy of God’s love, and turns into a divine-human love.